Determinants of Capital Structure: Evidence from Non-Financial Companies Listed on the Indonesia Stock Exchange - Robert Jao; Marselinus Asri; Anthony Holly; Jessica Juang (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2023)
This research is aimed to analyze the effect of effective tax rate, firm size, liquidity, financial flexibility, asset structure, growth opportunities, risk, profitability, asset utilization ratio, and ownership structure on capital structure. The theory used in this research is trade-off theory and pecking order theory. The data source in this research is the annual financial reports of non-financial companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2020. The sample selected using purposive sampling method. The results of this research indicate that the effective tax rate has a negative and insignificant effect on capital structure. Firm size, asset structure, and growth opportunities have a significant positive effect on capital structure. Liquidity, financial flexibility, profitability, and electoral structure have a significant negative effect on capital structure. Risk and asset utilization ratio have positive and insignificant effect on capital structure.